Chemical process design and integration - Smith, Robin (New Delhi: Wiley India Pvt. Ltd., 2015)
"Written by a highly regarded author with industrial and academic experience, this new edition of an established bestselling book provides practical guidance for students, researchers, and those in chemical engineering. The book includes a new section on sustainable energy, with sections on carbon capture and sequestration, as a result of increasing environmental awareness; and a companion website that includes problems, worked solutions, and Excel spreadsheets to enable students to carry out complex calculations"--
"The book provides a practical guide to chemical process design and integration for students and practicing process engineers in industry"--
Includes bibliographical references and index.
Keywords: Chemical processes; TECHNOLOGY & ENGINEERING / Chemical & Biochemical